CERITA HUMOR PAK ANDIR - Rohim, Rohim (ATAVISME, 2014)
This study attempts to describe the meaning of comic tale "Pak Andir" with the perspective of hermeneutics. This study is focused on exploring the main character with the theory of functional models and aktan, developed by Greimas. The source of data is the story of "Pak Andir" from the community of South Bengkulu. From the analysis, it is concluded that the behavior of the husband as the central character has made the wife a victim. The husband?s arrogance in strictly practicing the patriarchal tradition makes the wife have no courage to be herself. The wife?s claim at the end of the story is a positive thing, but it's too late. As a form of appreciation of literary work, the meaning of these stories need to be disseminated to the public, especially the residents in Bengkulu, that the husband and wife?s attitudes ares incorrect and need to be avoided. This study attempts to describe the meaning of comic tale "Pak Andir" with the perspective of hermeneutics. This study is focused on exploring the main character with the theory of functional models and aktan, developed by Greimas. The source of data is the story of "Pak Andir" from the community of South Bengkulu. From the analysis, it is concluded that the behavior of the husband as the central character has made the wife a victim. The husband?s arrogance in strictly practicing the patriarchal tradition makes the wife have no courage to be herself. The wife?s claim at the end of the story is a positive thing, but it's too late. As a form of appreciation of literary work, the meaning of these stories need to be disseminated to the public, especially the residents in Bengkulu, that the husband and wife?s attitudes ares incorrect and need to be avoided Key Words: comic tale; aktan model; functional model; hermeneutic Abstrak: Penelitian ini berusaha mendeskripsikan makna cerita humor ?Pak Andir? dengan perspektif hermeneutika. Kajian ini difokuskan untuk mengeksplorasi tokoh utama cerita dengan teori aktan dan model fungsional yang dikembangkan oleh Greimas. Sumber data penelitian ini adalah cerita ?Pak Andir? yang berasal dari masyarakat Bengkulu Selatan. Dari hasil pembahasan diperoleh simpulan bahwa perilaku suami sebagai tokoh sentral mengakibatkan istri menjadi korban. Keangkuhan suami dalam memegang teguh tradisi patriarkat membuat istri tidak berani menjadi diri sendiri. Gugatan sang istri pada akhir cerita merupakan hal positif, tetapi sudah terlambat. Sebagai wujud apresiasi terhadap karya sastra, makna cerita ini perlu disebarluaskan ke masyarakat khususnya warga Bengkulu, bahwa sifat?sifat suami istri itu keliru dan perlu dihindari